Popkultur als Herausforderung für die Kirchenmusik - Schroeter-Wittke, Harald (Liturgie und Kultur)

Gleichnis der Welt in Tönen. Zum 100. Todestag von Gustav Mahler - Schroeter-Wittke, Harald (Praktische Theologie)

Carla's Christmas Carols. Carla Bleys unorthodoxe Weihnacht - Schroeter-Wittke, Harald (Praktische Theologie)

Protestsongs.de - Schroeter-Wittke, Harald (Praktische Theologie)

"So reden wir immer!". Der Einfluss der Medien auf das Sprachverhalten junger Migranten in Deutschland - Günesli, Habib (tv diskurs)
Neue Medien eröffnen neue Möglichkeiten der Kommunikation und bringen neue sprachliche Erscheinungsformen zutage. Im Rahmen seiner Wissenschaftlichen Hausarbeit für die Erste Staatsprüfung für das Lehramt an Grund- und Hauptschulen hat sich der Autor mit dem Mediennutzungsverhalten und dessen Auswirkung auf die Sprachkompetenz junger türkischer Migranten beschäftigt.

Photocurrents in semiconductor carbon nanotubes with spin-orbit interaction - Meier, Torsten; Liu, Hong; Duc, Huynh Thanh; Schumache, Stefan (75. Annual meeting of the DPG and combined DPG Spring meeting)
In recent years, single-walled carbon nanotubes (SWCNTs) have received widespread attention due to their perfect quasi-one-dimensional structure and unique physical properties, as well as their potential for applications. In the present work, we calculate the band structure of SWCNTs using an atomistic tight-binding model including spin-orbit interaction. We combine this approach with a many-particle calculation of the nonlinear optical response using multi-band semiconductor Bloch equations. We show that, for SWCNTs lacking inversion symmetry, the intrinsic spin-orbit interaction can give rise to single-color photoinduced charge and spin currents. In particular, we study the influence of excitonic effects on these photoinduced currents and draw the analogy to recent investigations on single-color injection of photocurrents in semiconductor quantum wells.

Analysis of multidimensional Fourier transform spectroscopy for semiconductors with a phenomenological level model - Meier, Torsten; Wiebeler, Christian; Reichelt, Matthias (75. Annual meeting of the DPG and combined DPG Spring meeting)
Optical two-dimensional Fourier transform spectroscopy has been used to study the properties of semiconductor nanostructures in four-wave-mixing like experiments. Applying a phenomenological level model, we numerically and analytically analyze the main features of excitonic and biexcitonic contributions in a semiconductor quantum well by solving the optical Bloch equations. The method is extended to three-dimensional Fourier transform spectroscopy to investigate a recent experiment.

Extreme nonlinear optics in semiconductors with shaped laser pulses - Meier, Torsten; Reichelt, Matthias; Walther, Andrea (75. Annual meeting of the DPG and combined DPG Spring meeting)
If a two-level system is excited with an intense light field of several times the Rabi frequency, the well-known Mollow triplets appear in the emitted radiation spectrum. We show that the pattern of the emission spectrum can be changed by using appropriately shaped laser pulses. The effect is also observable for a more realistic description of a semiconductor system.

„Kutte & Co.“ – Zur textilen SchriftBildlichkeit des Heavy Metals - Eckel, Julia (Metal Matters – Heavy Metal als Kultur und Welt)

Tilting on non–commutative rational projective curves - Burban, Igor; Drozd, Yu. (Mathematische Annalen)

Mars-Viskurse. De- und Re-Kontextualisierungen von wissenschaftlichen Bildern - Adelmann, Ralf (Blickregime und Dispositive audiovisueller Medien)

Von der Freundschaft in Facebook - Adelmann, Ralf (Generation Facebook. Über das Leben im Social Net)

"Oh, Oh, Oh, let's count some more." Hochschulrankings als mediale Form - Adelmann, Ralf (Zeitschrift für Medienwissenschaft 1/2011)

Supportive and hindering factors to a sustainable implementation of ICT in schools - Eickelmann, Birgit (Journal for Educational Research Online/Journal für Bildungsforschung Online)

Restructuring educational systems to move into the digital age. Report of EduSummIT 2011 - Davis, Niki; Eickelmann, Birgit; Schulz-Zander, Renate (International Summit of ICT in Education: Building a Global Community of Policy-Makers, Educators, and Researchers to Move Education into the Digital Age)

Wirkungen digitaler Medien - Herzig, Bardo; Grafe, S. (Schule in der digitalen Welt. Medienpädagogische Ansätze und Schulforschungsperspektiven)

Medienkompetenz – Grundbegriffe, Kompetenzmodelle, Standards. - Herzig, Bardo; Grafe, S. (Kompetenzorientierung in Schule und Lehrerbildung. Perspektiven der bildungspolitischen Diskussion, der Bildungsforschung und der Mathematik-Didaktik)

Zukunftsfähige Lernkultur - Herzig, Bardo; Grafe, S. (Bildung Spezial. Friedrich Jahresheft 3/2011)

How Hydrogen Bonds Influence the Mobility of Imidazolium-Based Ionic Liquids. A Combined Theoretical and Experimental Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Lingscheid, Y.; Giernoth, R.; Sangoro, J.; Kremer, F.; Naumov, S.; Iacob, C.; Kärger, J.; Valiullin, R.; Kirchner, B. (J. Phys. Chem. B)

Performance of Quantum Chemically Derived Charges and Persistence of Ion Cages in Ionic Liquids. A Molecular Dynamics Simulations Study of 1-n-Butyl-3-Methylimidazolium Bromide - Kohagen, M.; Brehm, Martin; Thar, J.; Zhao, W.; Müller-Plathe, F.; Kirchner, B. (J. Phys. Chem. B)